Inter ocean basin moisture fluxes and the onset of the summer rainy season over southern Mexico - Magaña, Víctor; Diaz, Sonia (Frontiers in Climate, 2022)
The onset of the rainy season in monsoonal climates is a key element for the development of water related activities. In southern Mexico, it starts in late May or early June, while in western and northwestern part of the country in begins between early and mid-July. Previous studies indicate that it depends on the meridional position of the eastern Pacific Inter Tropical Convergence Zone (ITCZ). The present analysis shows that it also depends on the longitudinal position of the center of maximum convective activity in the ITCZ, which induces a quasi-stationary low-level cyclonic circulation that results in moisture fluxes to the Mexican Pacific coast and rains. The Caribbean Low-Level Jet (CLLJ) is a mechanism that modulates inter ocean basin moisture fluxes into the eastern Pacific ITCZ and the location of the maximum convective activity in this system. We propose that the sequence of events that leads to the onset of the rainy season in southern Mexico is: i) an episode of strong moisture flux from the Caribbean Sea into the eastern Pacific ITCZ, ii) a region of intense convective activity in the ITCZ that triggers a quasi-stationary low-level cyclonic circulation which in turn, induces moisture flux into southern Mexico, and iii) the development of convective activity in southern Mexico that determines the onset of the rainy season. The intensification of the CLLJ from June to July also results in a westward displacement of the region of maximum convection within the ITCZ that leads to changes in the atmospheric circulations and moisture fluxes that determine the onset of the rainy season at higher latitudes in the Mexican Pacific coast.